Strategi Komunikasi Pondok Pesantren untuk Menumbuhkan Minat dan Bakat Santri dalam Berwirausaha (Studi Kasus di Pondok Pesantren Mahasiswa Entrepreneur Nuris 2 Jember) - Nasirudin Al Ahsani; Halimatus Sa'diyah (Icon: Islamic Communication and Contemporary Media Studies, 2022)
An institution must have goals and characteristics that distinguish it from other institutions. To achieve this goal, an institution, especially Islamic boarding schools, certainly requires a strategy, one of the strategies needed is a well-planned and correct communication strategy. Communication strategies are needed by Islamic boarding schools, especially regarding activities, such as entrepreneurial activities. Among the many Islamic boarding schools that equip their students to create generations of entrepreneurs is the Nuris 2 Jember Entrepreneurial Student Islamic Boarding School. The focus of the problems studied are: 1) How is the communication strategy at the Nuris 2 Jember Entrepreneur Student Islamic Boarding School to foster students' interests and talents in entrepreneurship? 2) What are the inhibiting and supporting factors of entrepreneurial activities at the Nuris 2 Jember Entrepreneur Student Islamic Boarding School to foster students' interest and talents in entrepreneurship? This research uses descriptive qualitative method. through observation, interviews, and documentation. The conclusion of the research: the strategy used by Islamic boarding schools is by inviting students directly about entrepreneurship. The first is by delivering material to the students and the second is by direct practice in the field. Then the inhibiting factor that occurs is the lack of maximum communication carried out by the tutor when carrying out actions or practicing in the field. While the supporting factors are communication goals, selection of media in communication, assessment of messages conveyed, and the role of communicators in entrepreneurial activities that are appropriate and quite good.